Additive Manufacturing of TiC/Steel Composites Using Electron Beam Melting and In Situ Infiltration - Chen, Yong; Fu, Zongwen; Ye, Jihui; Wahlmann, Benjamin; Körner, Carolin (Advanced Engineering Materials, 2024)
Cemented carbides containing titanium carbide (TiC), characterized by low specific weight, superior hardness, and excellent high-temperature resistance, are widely used as wear-resistant cutting tools and brake discs. Instead of using conventional powder metallurgical approaches, composites comprising TiC and stainless steel are fabricated in this study by means of an innovative method combining electron beam powder bed fusion (PBF-EB) and in situ liquid metal infiltration. For PBF-EB, a pure TiC powder as feedstock and a stainless steel plate as substrate are used, respectively. Owing to the high processing temperature in the hatching area, the TiC particles are inhomogeneously sintered. Simultaneously, an in situ infiltration of liquid steel into the pores between TiC particles takes place during PBF-EB, forming a dense and crack-free composite material containing ≈68% TiC. The electrical properties of the raw TiC powder are investigated at different temperatures to optimize the process parameters ensuring high process stability during PBF-EB. The microstructure and mechanical properties (compression strength, hardness, and fracture toughness) of the PBF-EB-produced TiC/steel composite are analyzed.
CRIS-Team Scopus Importer:2024-04-12
Keywords: cemented carbide; composite materials; electron beam powder bed fusion; mechanical properties; titanium carbide